STUDI TENTANG RENDAHNYA KEMAMPUAN MEMBACA PESERTA DIDIK KELAS II SDN-8 MENTENG PALANGKA RAYA - Suniati Suniati (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This study aims to determine the low reading ability on the second grade students of SDN-8 Menteng Palangka Raya. This research using descriptive method. The population in this study are all students class II. That is divided into two classes, namely II-A, which amounted to 18 people and II-B, amounting to 16 people. The sample in this study is the total number of study population which amounted to 34 students. The result of dominant factor until the very dominant factor is the low reading ability of students of second grade students of SDN-8 Menteng Palangka Raya, that students at reading not pay attention to punctuation there are 34 students or 100%. Learners do not understand the sentence that he read there are 32 students or 94.11%. Learners do not read smoothly there are 22 students or 64.70%. Students at reading reading eliminate letters or words there are 22 students or 64.70%, and learners mistake pronounce letters that sound like a letter b with p There are 21 students or 61.77%.